Incidence of Hepatitis E Infection in American Patients With Suspected Drug-Induced Liver Injury Is Low and Declining: The DILIN Prospective Study - Fontana, Robert John; Engle, Ronald E.; Hayashi, Paul H.; Gu, Jiezhun; Kleiner, David E.; Nguyen, Hahn; Barnhart, Huiman; Hoofnagle, Jay H.; Farci, Patrizia (The American journal of gastroenterology, 2022)
Hepatitis E virus (HEV) infection rarely causes icteric hepatitis, yet 10%-40% of adult Americans have serological evidence of previous infection. The aim of this study was to investigate the incidence, presentation, and outcome of acute and previous HEV infection in a large cohort of patients with suspected drug-induced liver injury (DILI). Serum samples from 2012 patients enrolled in the DILI Network were tested for anti-HEV immunoglobulin G (IgG). Those with detectable anti-HEV IgG underwent testing for anti-HEV IgM; those with detectable anti-HEV immunoglobulin m (IgM) were tested for HEV RNA. Anti-HEV IgG was detected in 407 (20%) patients and associated with increasing subject age and earlier year of enrollment. The median age of seropositive subjects was more than a decade higher than seronegative subjects (59.8 vs 48.7 years). The overall prevalence of anti-HEV declined from 22% (2004-2011) to 18% (2012-2019), suggestive of a cohort effect. The frequency of acute hepatitis E (median ALT = 1231 IU/L) also decreased from 3% (2004-2008) to 1.2% (2009-2013) to 0.6% (2014-2019). These results suggest that acute HEV infection is usually subclinical and was much more frequent in this cohort before 2004. Acute HEV infection accounts for less than 1% of suspected American DILI cases and is more frequent in older men. Previous HEV infection is also most commonly seen in older individuals. Clinicians should consider testing for unsuspected acute HEV infection in older adult patients with acute hepatocellular DILI and jaundice.